Party System Changes and Challenges to Democracy Slovenia in a Comparative Perspective - Fink-Hafner, Danica (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book focuses on the nexus between "party system stability" and "democratic consolidation", using Slovenia as a case study. Its findings are presented from a comparative perspective to illustrate the commonalities and differences found in research on Central European post-socialist countries and former Yugoslav countries. On the one hand, Slovenia's characteristics (including the characteristics of its transition to democracy) are far more similar to those of Central European post-socialist countries than Western Balkan countries. On the other, Slovenia shares some similarities with other parts of the former Yugoslavia - especially its experiences with the political system of socialist self-management, elements of a market economy under socialism, and war following the end of socialism (albeit the conflict in Slovenia was very short and rather mild in comparison to those in other parts of socialist Yugoslavia). Slovenia's experiences with rapid but limited democratic backsliding under the Janša government (March 2019-June 2022) were halted by the 2022 national election - in contrast to the more widely known cases of Hungary and Poland, where such backsliding took place incrementally over a longer period of time that included several election cycles. Danica Fink-Hafner is Professor at the University of Ljubljana, Slovenia.